2016
DOI: 10.1038/bjc.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on faecal MMP-9: a new noninvasive diagnostic marker of colorectal cancer

Abstract: Background:Colorectal cancer (CRC) is one of the leading malignancies worldwide, therefore cheap noninvasive screening methods are of great importance. Matrix-metalloproteinase-9 (MMP-9) has a role in the progression of CRC, and its level is elevated in tumour biopsies. Faecal MMP-9 levels are increased in active ulcerative colitis patients, but in CRC patients, they have never been measured. We aimed to assess the faecal MMP-9 levels in patients undergoing total colonoscopy according to endoscopic and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…Our data showed that PLS1 is highly expressed in CRC tissues with the metastasis of CRC and shows potential to be a prognostic biomarker. [18][19][20]32 As expected, MMP9 and MMP2 were regulated by PLS1, which depended on the activation of the ERK signal. This We have previously demonstrated that IQGAP1 knockdown significantly suppresses CRC cell migration and invasion in vitro.…”
Section: Discussionsupporting
confidence: 73%
“…Our data showed that PLS1 is highly expressed in CRC tissues with the metastasis of CRC and shows potential to be a prognostic biomarker. [18][19][20]32 As expected, MMP9 and MMP2 were regulated by PLS1, which depended on the activation of the ERK signal. This We have previously demonstrated that IQGAP1 knockdown significantly suppresses CRC cell migration and invasion in vitro.…”
Section: Discussionsupporting
confidence: 73%
“…It is an attractive pan-pathology immune biomarker and target for the treatment of numerous diseases and is a central interactor for numerous other pan-cancer biomarkers we have identified herein. MMP-9 is an attractive pan-pathology biomarker because its elevated expression can be detected in tumors but also by less invasive methods examining blood and by completely noninvasive methods examining urine, fecal samples, tears, and exhaled breath condensate (76)(77)(78). Because MMP-9 expression is controlled by circadian rhythm, diurnal variations may be responsible for its initial immune deregulation in patients.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, matrix metalloproteinase enzyme family, play a key role in the proteolytic degradation of ECM and, therefore, cancer cells metastasis [34,48]. MMP-9 and MMP-2 are the members of this family that increase invasion of the tumour [49].…”
Section: Discussionmentioning
confidence: 99%
“…An important enzyme family called matrix metalloproteinase is involved in the proteolytic degradation of ECM [33]. Degradation of the ECM is a vital step in normal physiological processes such as embryo development as well as pathogenic processes, such as metastasis and angiogenesis in many cancers including melanoma [34]. Matrix metalloproteinase-2 (MMP)-2 and MMP-9 are the members of the MMP family that increase invasion of the tumour by the destruction of extracellular matrix and provide access of metastatic cancer cells to the bloodstream [35,36].…”
Section: Introductionmentioning
confidence: 99%